AN INVESTIGATION OF IDEOLOGICAL TEACHING IN QUALITY-ORIENTED EDUCATION: A CASE STUDY OF THE ADDIE MODEL IN - Huang Yanyun,; Suyansah Swanto,; Wardatul Akmam Din,; Wirawati Ngui Yi Xe, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This research delves into the effective application of the ADDIE model within the "Intercultural Communication" course, focusing on ideological teaching with a quality-oriented perspective. The primary goal is to analyze challenges in integrating ideological education and explore how the ADDIE model's five stages can be adeptly employed. Additionally, the study adopts a blended approach, incorporating online and offline teaching, along with the "dual-teacher classroom" method, aiming to enhance the pedagogical framework in the "Internet+" education environment. Through qualitative method research, qualitative data from interviews with instructors and students provide insights into their experiences. Empirical findings affirm that the ADDIE model significantly aids in achieving curriculum-specific ideological objectives, providing valuable insights for instructional design in ideological education and serving as a reference for diverse courses in Chinese universities. The study also offers practical implications for policymakers and academics aiming to improve instructional practices in the educational landscape.